Comparisons of morphology and esterase levels between Blattella germanica and Blattella nipponica (Blattodea: Blattellidae). Issue 3 (27th November 2016) - Kim, Juil; Kwon, Min; Maharjan, Rameswor; Kim, Gil‐Hah
Abstract: The habitat of the cockroach varies by species. The German cockroach, Blattella germanica, lives in human dwellings, while the Japanese field roach, Blattella nipponica, lives in a mountainous region. Based on phylogenetic analysis of mt COI, the two species are closely related to each other and B. germanica is divergent from wild species such as B. nipponica. Their habitats and walking speed differ even though the two species have similar morphology. We hypothesized that habitats might influence walking speed by changes to appendage morphology and enzyme‐based physiological differences. We compared the length of the appendages and differences in a multifunctional enzyme superfamily, the esterases (EST, EC 3.1), including acetylcholinesterase (AChE, EC 3.1.1.7), which is related to central nervous system function. We found that phenotypes such as appendage length and esterase isozyme expression were clearly different between the two species. These differences might be responsible for the observed difference in walking speed.